Technical aspects in effective frequency spectrum pricing - Muhammed M. Abdelhaseeb; Fadel Digham (International Telecommunications Society (ITS), 2019)
Microwave spectrum has been the primary solution for the rapid and cost-effective rollout of mobile backhaul infrastructure. Most of the mobile sites worldwide today are connecting via Microwave (MW) or Millimeter Wave (mmW) radio links. The evolution from 4G towards 5G presents significant challenges to all transport technologies and wireless ones make no exception. The goal of this paper is to investigate technical factors that can be used by regulators in order to achieve an effective frequency spectrum-pricing model applied for Microwave links. Especially in this stage, while all mobile operators need a huge bandwidth of spectrum to accommodate and backhaul high data rates for 4G and 5G applications. There are several strategies in theory that could be used by regulators in order to determine appropriate frequency spectrum fees. In addition, there are different factors when it comes to evaluating the value of spectrum. Many aspects and issues are facing regulators for designing an effective spectrum management, such as efficient spectrum usage, public and social benefits, introduction of new technologies, licensing regimes, etc. Therefore, in this paper we are looking for some technical factors that may be taken into account in order to have an effective frequency spectrum-pricing model for Microwave links.
Keywords: 330; Microwave; Spectrum price; Spectral efficiency; Technology factor; Data rate; XPIC; MIMO